The Problem of a Variant and Psychology of Folk Verbal Creation under Conditions of Local Tradition - Mitropolskaja, N. (Literatūra, 1975)
The yearly expeditions to the Zarasai, Ignalina, Anykščiai, Jonava, Rokiškis and other districts of the Lithuanian S.S.R. made it possible to record some valuable folk - lore samples among the Russian old – resident population (1928 singers and narrators are Russians while 22, whose songs and narratives were performed in Russian, are Polish, Lithuanians or Byelorussians).The originality of the Russian folk -- lore in Lithuania is determined by the existence of the old - resident Russian population isolated from the bulk of the Russian nation as well as by constant contacts of the former with the main population of the Republic. The pieces recorded are characterired by a good preservation, archaic features, artistic completeness of the verbal compositions of different genres and by the acquisition of the folk - lore values of the neighbouring peoples. The presence of a living folk - lore tradition in the above districts made it possible to record rare pieces of calendar - ritual and ruptial songs as well as numerous well - preserved love songs, popular soldier songs that have vanished at many places of occurrence of the Russian folk- ballad. Besides, many varied proverbs and riddles have been recorded. The popular tales recorded are found to be multi - plot ones (180 tale - plots and 1420 variants performed by 172 narrators have been recorded). The including of some Lithuanian and Polish plots in the Russian repertory is considered to be another characteristic feature of the tales.
Keywords: -